Vizsgálat egy szegedi dísznövény-kereskedésben - Zsótér, Brigitta; Hajnal, Helga (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
Customers of the examined flower shop are mostly local inhabitants who frequent the place at least on a monthly basis. The market garden do not advertised itself, most of the customers heard about it from other people. The market garden has recently updated its website about which its customers should be informed since a great proportion has never seen it, so they cannot utilize the available services. The respondents are mostly satisfied with the quality of products sold there and made some suggestions to eliminate some smaller mistakes. The planned Internet flower-delivery service is welcomed so the market garden gives the service a start soon. According to the survey there should be more , DIY"-activities, where everybody could made his/her own wreaths for Advent or knockers.